Ultra-black carbon powder with infrared / visible light dual-band absorption performance and morphology-controllable preparation method and application of ultra-black carbon powder

By self-assembly forming a hydrogen bonded organic frame and coating a phenolic resin, ultra-black carbon powder with a complex porous hollow structure was prepared, which solved the problems of complex preparation and insufficient performance of existing ultra-black carbon powder, and achieved the effect of efficient absorption and simplified process in infrared/visible light dual-band.

CN119569031AActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411766626.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing ultra-black toner preparation process is complex, the production cost is high, and it is difficult to achieve broadband absorption in both infrared and visible light, which limits its practical application potential.

Method used

Bowl and cage-shaped ultra-black toner with complex porous hollow structures were prepared by self-assembly between melamine and cyanic acid, and by coating and calcining of phenolic resin.

Benefits of technology

The infrared/visible light dual-band absorption performance of ultra-black carbon powder is achieved, with an absorption rate of 99.7% or above, simplifying the preparation process, reducing costs, and improving the processability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569031A_ABST
    Figure CN119569031A_ABST
Patent Text Reader

Abstract

The invention discloses ultra-black carbon powder with infrared / visible light dual-band absorption performance and a morphology-controllable preparation method and application thereof. The invention belongs to the field of preparation of ultra-black carbon powder. The invention aims to solve the technical problems that the existing ultra-black carbon powder is complex to prepare and high in production cost, and the performance needs to be improved. The method comprises the following steps: firstly, respectively dissolving melamine and cyanuric acid in dimethyl sulfoxide or ethylene glycol, then dropwise adding a melamine solution into a cyanuric acid solution, and stirring for reaction or stirring for reaction under a heating condition to obtain a hydrogen bond organic framework; and adding the hydrogen bond organic framework into an absolute ethyl alcohol solution of phenolic resin, stirring for reaction, centrifuging, drying a solid product, and calcining in a protective atmosphere to obtain the ultra-black carbon powder. The method is simple in process and low in cost. The obtained ultra-black carbon powder is adjustable in structure, stable in performance, good in dispersity in high-molecular organic rubber and high in machinability. The material is used for absorbing visible light and infrared waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ultra-black carbon powder preparation, and specifically relates to an ultra-black carbon powder with infrared / visible light dual-band absorption performance and a morphology-controllable preparation method and application thereof. Background Art

[0002] In the aerospace field, the use of high-precision optical equipment will be interfered by stray light, resulting in reduced detection signal-to-noise ratio, sensitivity and inversion accuracy of the equipment. Ultra-black coating is an effective stray light elimination coating that can absorb and weaken non-imaging sensitive light within a specific wavelength range in the space environment, thereby achieving efficient removal of stray light.

[0003] Carbon materials generally have a large conjugated system and a moderate free electron density, and are a popular ultra-black material. Adding ultra-black carbon powder to a high molecular polymer to prepare a composite coating can achieve a light-absorbing coating with high efficiency, high chemical stability, light resistance, weather resistance, and light weight. However, the preparation processes of traditional carbon-based ultra-black materials such as carbon nanotube arrays and carbon aerogels are very complicated, and it is not easy to prepare them into processable ultra-black coatings. In addition, there are some ultra-black carbon powders. Although their processability has been improved, in order to obtain a hollow light-trapping structure, these schemes usually use a hard template method to prepare samples, and it is inevitable to use high-risk chemical reagents such as strong acids and strong alkalis, which not only greatly increases production costs, but also causes environmental pollution problems. At the same time, due to the simple structure, these ultra-black carbon powders are usually difficult to achieve broadband absorption covering both infrared and visible light bands. The above problems limit their practical application potential. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems of complex preparation, high production cost and performance improvement of existing ultra-black carbon powder, and to provide an ultra-black carbon powder with infrared / visible light dual-band absorption performance and a controllable morphology preparation method and application thereof.

[0005] One of the purposes of the present invention is to provide a method for preparing ultra-black carbon powder with infrared / visible light dual-band absorption performance in a controllable manner, the method being carried out in the following steps:

[0006] S1: Melamine and cyanuric acid are dissolved in dimethyl sulfoxide or ethylene glycol respectively, and then the melamine solution is added dropwise to the cyanuric acid solution, and the mixture is stirred for reaction. When the melamine solution is dissolved in ethylene glycol, the mixture is stirred for reaction under heating conditions. After the reaction is completed, the mixture is washed with hot water by suction filtration and freeze-dried to obtain a hydrogen-bonded organic framework.

[0007] S2: adding the hydrogen-bonded organic framework to an anhydrous ethanol solution of phenolic resin, stirring the reaction, drying the solid product after centrifugation, and calcining under a protective atmosphere to obtain ultra-black carbon powder.

[0008] It is further defined that the mass ratio of melamine to cyanuric acid in S1 is 1.5:(1-2).

[0009] It is further defined that when S1 is dissolved in dimethyl sulfoxide, the concentration of the melamine solution is 0.04-0.06 g / mL, and the concentration of the cyanuric acid solution is 0.05-0.07 g / mL.

[0010] It is further defined that when S1 is dissolved in ethylene glycol, the concentration of the melamine solution is 0.02-0.03 g / mL, and the concentration of the cyanuric acid solution is 0.005-0.015 g / mL.

[0011] It is further defined that the reaction in S1 is stirred at 70-90° C., and the stirring reaction time is 5-10 min.

[0012] It is further defined that S1 is washed with hot water at 70-90°C.

[0013] It is further defined that the mass ratio of the hydrogen-bonded organic framework to the phenolic resin in S2 is 0.5:(0.3-0.5).

[0014] It is further defined that the concentration of the phenolic resin in the anhydrous ethanol solution of the phenolic resin in S2 is 6-10 mg / mL.

[0015] It is further defined that the reaction in S2 is stirred for 10-12 hours.

[0016] It is further defined that the drying temperature in S2 is 50-70°C.

[0017] The calcination procedure in S2 is further defined as follows: first increase the temperature to 350-450°C at a rate of 1-3°C / min, keep warm for 1-2.5 hours, then increase the temperature to 500-550°C, keep warm for 2-4 hours, continue to increase the temperature to 700-800°C, keep warm for 1.5-4 hours, and cool to room temperature with the furnace after the insulation is completed.

[0018] The second object of the present invention is to provide a bowl-shaped super black carbon powder prepared by the above method, which is obtained when dissolved in dimethyl sulfoxide and has an irregular porous hollow spherical shape with openings on the sphere.

[0019] It is further defined that the bowl-shaped super black carbon powder has a diameter of 700-950nm and an opening diameter of 200-300nm.

[0020] The third object of the present invention is to provide a cage-like super black carbon powder prepared by the above method, which is obtained when dissolved in ethylene glycol and has an irregular porous hollow spherical shape.

[0021] It is further defined that the diameter of the cage-shaped super black carbon powder is 1-2.5 μm.

[0022] A fourth object of the present invention is to provide an ultra-black composite coating based on the above-mentioned bowl-shaped ultra-black carbon powder and cage-shaped ultra-black carbon powder.

[0023] A fifth object of the present invention is to provide a method for preparing an ultra-black composite coating based on the above-mentioned bowl-shaped ultra-black carbon powder and cage-shaped ultra-black carbon powder, the method steps are as follows:

[0024] The ultra-black carbon powder is mixed with PDMS, acetone and a curing agent, and then allowed to stand in a vacuum oven, and then heated and cured to obtain an ultra-black composite coating.

[0025] A sixth object of the present invention is to provide an application of the above-mentioned ultra-black composite coating in absorbing visible light and infrared waves.

[0026] Compared with the prior art, the present invention has the following significant effects:

[0027] The present invention provides two structurally adjustable ultra-black carbon powders with high light absorption performance and a preparation method thereof. The method first utilizes the self-assembly between melamine and cyanuric acid to obtain a hydrogen-bonded organic framework powder, and at the same time, by adjusting the polarity of the reaction solvent, the hydrogen bond length and angle in the hydrogen-bonded organic framework can be effectively regulated, thereby achieving control over its structure. Further, the phenolic resin molecules are coated by secondary hydrogen bonding as a carbon source for subsequent calcination. During calcination, the melamine-cyanuric acid supramolecules undergo a dehydration polycondensation reaction to first form a carbon nitride (C3N4) phase composed of triazine rings. When the calcination temperature rises, the triazine rings are unstable due to their sp 2 The hybrid CN bond is destroyed and begins to degrade until it is completely decomposed into gaseous carbon. At the same time, the carbon atoms in the outer phenolic resin molecules continue to rearrange, and the degree of carbonization continues to increase, thus eventually obtaining a complex porous hollow structure. Its innovative points are as follows:

[0028] (1) The present invention utilizes a hydrogen-bonded organic framework precursor conversion strategy to obtain ultra-black carbon powder after calcination. The material structure is controllably regulated by simple reaction solvent control, and two types of bowl-shaped MB and cage-shaped MC ultra-black carbon powders with stable performance are constructed, with simple process and low cost.

[0029] (2) The bowl-shaped MB and cage-shaped MC ultra-black carbon powders prepared in the present invention have a complex light-trapping structure. The micron / submicron-level inner cavity matches the wavelength of infrared / visible light. The porous irregular morphology is conducive to reducing the reflection of incident light and enhancing multiple scattering, thereby achieving strong light absorption. At the same time, the powder has good dispersibility in polymer organic rubber and has high processability.

[0030] (3) The ultra-black carbon powder prepared by the present invention has excellent infrared / visible dual-band absorption performance. Thanks to the unique hierarchical structure, the maximum absorption rates in the short-wave / medium-wave / long-wave infrared light ranges reach 99.7%, 97.6% and 98.7% respectively, and the maximum absorption rate for visible light is about 99.72%, achieving efficient dual-band absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Scanning electron microscope (SEM) images and transmission electron microscope (TEM) images of the bowl-shaped MB and cage-shaped MC super black carbon powders prepared in Examples 1-2; (a)-MB-SEM, (c)-MB-TEM, (b)-MC-SEM, (d)-MC-TEM;

[0032] Figure 2 (a) is an optical photograph of the bowl-shaped MB and cage-shaped MC ultra-black carbon powders prepared in Example 1-2 at a brightness of -10000 lumens in a high dynamic range camera shooting mode; Figure 2 (b) is a physical photo of the ultra-black composite coating obtained in Example 1;

[0033] Figure 3 X-ray diffraction (XRD) patterns of the bowl-shaped MB and cage-shaped MC ultra-black carbon powders prepared in Example 1-2;

[0034] Figure 4 The visible light excited Raman spectra of the bowl-shaped MB and cage-shaped MC ultra-black carbon powders prepared in Example 1-2;

[0035] Figure 5 The reflectivity of the bowl-shaped MB and cage-shaped MC super black carbon powders prepared in Examples 1-2 in the long-wave infrared and mid-wave infrared bands;

[0036] Figure 6 The reflectivity of the bowl-shaped MB and cage-shaped MC ultra-black carbon powders prepared in Example 1-2 in the ultraviolet-short-wave infrared wavelength range;

[0037] Figure 7 The reflectivity of the bowl-shaped MB and cage-shaped MC super black carbon powders prepared in Examples 1-2 in the visible light wavelength range. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0040] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0041] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0042] Embodiment 1:

[0043] The method for preparing the ultra-black composite coating based on the bowl-shaped ultra-black carbon powder in this embodiment is carried out according to the following steps:

[0044] (1) Take 1.50 g of melamine and add it to 30 mL of dimethyl sulfoxide, stir until it is completely dissolved, and obtain a melamine solution. Take 1.52 g of cyanuric acid and add it to 25 mL of dimethyl sulfoxide, stir until it is completely dissolved, and obtain a cyanuric acid solution. Add the obtained melamine solution dropwise to the obtained cyanuric acid solution, stir and react for 10 minutes, transfer the product to a vacuum filtration bottle, wash it with 80°C hot water, and freeze-dry it for 48 hours to obtain a hydrogen-bonded organic framework material.

[0045] (2) 0.5 g of the hydrogen-bonded organic framework product was added to 50 mL of anhydrous ethanol solution of phenolic resin (molecular weight 1000) with a concentration of 0.008 g / mL. The solid product was obtained by centrifugation after stirring for 12 h. The solid product was dried at 60 °C and then placed in a sealed porcelain boat. The solid product was calcined in an argon atmosphere using a tubular furnace. The product was first heated to 400 °C at a rate of 2 °C / min and kept warm for 2 h. The product was then heated to 530 °C at a rate of 1 °C / min and kept warm for 3 h. Finally, the product was heated to 750 °C at a rate of 1 °C / min and kept warm for 3 h. The product was then cooled to room temperature in the furnace and a bowl-shaped ultra-black powder was obtained, which was recorded as MB.

[0046] (3) Take 150 mg of super black powder MB, mix it with 3 g of PDMS, 0.3 g of acetone and 0.3 g of curing agent, and place it in a vacuum oven with a vacuum degree of 0.1 MPa for 30 min. Take out the mixture and add it to the mold, and put it in the vacuum oven again and cure it at 100 ° C for 1 h to finally obtain the super black composite coating.

[0047] Embodiment 2:

[0048] The preparation method of the ultra-black composite coating based on the cage-shaped ultra-black carbon powder in this embodiment is carried out according to the following steps:

[0049] (1) 1.50 g of melamine was added to 60 mL of ethylene glycol, and stirred at 80°C until completely dissolved to obtain a melamine solution. 1.52 g of cyanuric acid was added to 125 mL of ethylene glycol, and stirred at 80°C until completely dissolved to obtain a cyanuric acid solution. The obtained melamine solution was added dropwise to the obtained cyanuric acid solution, and the reaction was stirred at 80°C for 10 min. The product was transferred to a vacuum filtration bottle, washed with 80°C hot water, and freeze-dried for 48 hours to obtain a hydrogen-bonded organic framework material.

[0050] (2) Take 0.5 g of the hydrogen-bonded organic framework product and add it to 50 mL of anhydrous ethanol solution of phenolic resin (molecular weight 1000) with a concentration of 0.008 g / mL. After stirring for 12 h, centrifuge to obtain a solid product, dry it at 60 °C, then put it in a sealed porcelain boat, and calcine it in an argon atmosphere using a tubular furnace. First, heat it to 400 °C at a rate of 2 °C / min and keep it warm for 2 h, then heat it to 530 °C at a rate of 1 °C / min and keep it warm for 3 h, and finally, continue to heat it to 750 °C at a rate of 1 °C / min and keep it warm for 3 h, then cool it to room temperature with the furnace, and collect the cage-like ultra-black powder, which is recorded as MC.

[0051] (3) Take 150 mg of ultra-black powder MC, 3 g of PDMS, 0.3 g of acetone and 0.3 g of curing agent, mix them evenly, and place them in a vacuum oven with a vacuum degree of 0.1 MPa for 30 min. Take out the mixture and add it to the mold, and put it in the vacuum oven again and cure it at 100 ° C for 1 h to finally obtain an ultra-black composite coating.

[0052] Figure 1 a, c are the SEM images and TEM images of the bowl-shaped MB microparticles prepared in Example 1. It can be seen from the figures that the bowl-shaped MB microparticles are irregular porous hollow spheres as a whole, with a diameter of about 700-950nm, and have an obvious opening with an opening diameter of about 200-300nm.

[0053] Figure 1b and d are the SEM images and TEM images of the cage-like MC microparticles prepared in Example 2. It can be seen from the figures that the cage-like MC microparticles are also irregular porous hollow spherical in shape as a whole, but have a complete structure without an open structure, and have a diameter of about 2 μm.

[0054] Figure 2 a is a high dynamic range optical photograph of the bowl-shaped MB and cage-shaped MC super black carbon powder samples prepared in Example 1 and Example 2 at a brightness of 10,000 lumens. Compared with phthalocyanine-based black ink and commercial super black materials such as Musou Black 2.0 with an absorbance of 99.4% and Nacate Black 4.0 with an absorbance of 99.0%, the MB and MC super black carbon powders prepared in the present invention both exhibit higher black contrast under the naked eye.

[0055] Figure 2 b is a photo of the coating after the bowl-shaped MB super black carbon powder sample prepared in Example 1 was compounded with PDMS. It can be seen that the obtained coating still exhibits extremely high blackness.

[0056] Figure 3 The XRD spectra of the bowl-shaped MB and cage-shaped MC ultra-black carbon powders obtained in Example 1 and Example 2 show that both have typical amorphous characteristics. The diffraction peak near 2θ=25° comes from the (002) crystal plane of carbon, and the broad peak shape indicates that the order of carbon atoms is low.

[0057] Figure 4 : The Raman spectra of the bowl-shaped MB and cage-shaped MC super black carbon powders obtained in Example 1 and Example 2 show that the peak positions and peak shapes of the D peak and the G peak of the two materials are almost the same, and the half-peak width is also almost the same, which indicates that their microstructures are very consistent, with only a difference in shape. The integrated intensity of the D peak and the G peak is calculated to obtain I D / I G The ratios of I and B are 3.50 and 3.53, respectively, which again proves their highly similar microstructures. D / I G The value indicates that the degree of graphitization is very low.

[0058] Figure 5The reflectivity of the bowl-shaped MB and cage-shaped MC super black carbon powder obtained in Example 1 and Example 2 in the long-wave (8-14μm) infrared and medium-wave (3-5μm) infrared bands. According to Kirchhoff's theorem, the absorptivity and emissivity are equal under thermal equilibrium. Therefore, it can be seen that the maximum absorptivity of the bowl-shaped MB and cage-shaped MC super black carbon powder in the long-wave infrared band can reach 98.7%, and the absorptivity in the entire long-wave infrared band can reach an average of 98%. In the medium-wave infrared band, the absorptivity of both decreased to 97.6%. The absorptivity of the bowl-shaped MB in the entire medium-wave infrared band can reach 97.5%. Since the constructed bowl-shaped MB and cage-shaped MC particles are irregular in shape and have a porous hollow structure, it is beneficial for light waves to enter the interior of the material without emission. Subsequently, the strong light absorption in the long / medium-wave infrared band may come from the multiple scattering effect of light between particles.

[0059] Figure 6 The reflectivity of the bowl-shaped MB and cage-shaped MC super black carbon powders obtained in Example 1 and Example 2 in the range of ultraviolet light to short-wave infrared wavelengths shows that in the short-wave (850-2500nm) infrared band, the absorptivity of both is substantially greater than 99%, and the maximum absorptivity can reach 99.7%. The cage-shaped MC exhibits stronger short-wave infrared light absorption as a whole, which may be because the diameter of the cage-shaped MC (about 2μm) matches the wavelength, causing strong multiple reflections of light inside the particles, thereby achieving efficient short-wave infrared absorption.

[0060] Figure 7 The reflectivity of the bowl-shaped MB and cage-shaped MC super black carbon powders obtained in Example 1 and Example 2 in the visible light wavelength range shows that the reflectivity of both in the entire visible light band is less than 0.35%. For opaque objects, this means that the absorption rate of the bowl-shaped MB and cage-shaped MC super black carbon powders to visible light is higher than 99.65%, among which the maximum absorption rate of the bowl-shaped MB can reach 99.72%, which is higher than the 99.70% of the cage-shaped MC. This may be because the size of the bowl-shaped MB (700-800nm) is more compatible with the wavelength at this time, causing multiple reflections of light.

[0061] According to the above graphs and data analysis: The present invention constructs structurally adjustable ultra-black carbon powder, namely bowl-shaped MB and cage-shaped MC, through the hydrogen-bonded organic framework precursor conversion strategy. The complex irregular porous hollow structure promotes multiple reflections and multiple scatterings of light entering the material, achieving efficient visible light / infrared dual-band absorption. The excellent absorption performance, simple preparation process and low cost make the material have good application prospects, and at the same time provide good inspiration and reference for the structural design of carbon-based ultra-black materials.

[0062] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing ultra-black carbon powder with infrared / visible light dual-band absorption performance with controllable morphology, characterized in that: The method: S1: Melamine and cyanuric acid are dissolved in dimethyl sulfoxide or ethylene glycol respectively, and then the melamine solution is added dropwise to the cyanuric acid solution, and the mixture is stirred for reaction. When the melamine solution is dissolved in ethylene glycol, the mixture is stirred for reaction under heating conditions. After the reaction is completed, the mixture is washed with hot water by suction filtration and freeze-dried to obtain a hydrogen-bonded organic framework. S2: adding the hydrogen-bonded organic framework to an anhydrous ethanol solution of phenolic resin, stirring the reaction, drying the solid product after centrifugation, and calcining under a protective atmosphere to obtain ultra-black carbon powder.

2. The method according to claim 1, characterized in that The mass ratio of melamine to cyanuric acid in S1 is 1.5:(1-2). When dissolved in dimethyl sulfoxide, the concentration of melamine solution is 0.04-0.06 g / mL, and the concentration of cyanuric acid solution is 0.05-0.07 g / mL; when dissolved in ethylene glycol, the concentration of melamine solution is 0.02-0.03 g / mL, and the concentration of cyanuric acid solution is 0.005-0.015 g / mL. The reaction is stirred at 70-90°C, and the stirring reaction time is 5-10 min.

3. The method according to claim 1, characterized in that The mass ratio of the hydrogen-bonded organic framework and the phenolic resin in S2 is 0.5:(0.3-0.5), the concentration of the phenolic resin in the anhydrous ethanol solution of the phenolic resin is 6-10 mg / mL, the reaction is stirred for 10-12 hours, and the calcination procedure is: first increase the temperature to 350-450°C at a rate of 1-3°C / min, keep warm for 1-2.5 hours, then increase the temperature to 500-550°C, keep warm for 2-4 hours, continue to increase the temperature to 700-800°C, keep warm for 1.5-4 hours, and cool to room temperature with the furnace after the insulation is completed.

4. The bowl-shaped super black carbon powder prepared by the method according to any one of claims 1 to 3, characterized in that: When dissolved in dimethyl sulfoxide, the bowl-shaped ultra-black carbon powder is obtained, which is in the shape of an irregular porous hollow sphere with openings on the sphere.

5. The bowl-shaped super black carbon powder according to claim 4, characterized in that: The bowl-shaped super black carbon powder has a diameter of 700-950nm and an opening diameter of 200-300nm.

6. The cage-shaped super black carbon powder prepared by the method according to any one of claims 1 to 3, characterized in that: When dissolved in ethylene glycol, the cage-like ultra-black carbon powder is obtained, which is in the shape of irregular porous hollow spheres.

7. The cage-shaped super black carbon powder according to claim 6, characterized in that: The diameter of cage-shaped super black carbon powder is 1-2.5μm.

8. An ultra-black composite coating of ultra-black carbon powder prepared by the method according to any one of claims 1 to 3.

9. The method for preparing the ultra-black composite coating according to claim 8, characterized in that: The method: The ultra-black carbon powder is mixed with PDMS, acetone and a curing agent, and then allowed to stand in a vacuum oven, and then heated and cured to obtain an ultra-black composite coating.

10. Use of the ultra-black composite coating according to claim 8 in absorbing visible light and infrared waves.

Citation Information

Patent Citations

  • Red supramolecular graphite phase carbon nitride photocatalyst capable of improving visible light utilization rate and preparation method of red supramolecular graphite phase carbon nitride photocatalyst

    CN116099565A

  • Preparation method of carbon nitride with specific phase high crystallization and surface defect structure

    CN116199197A

  • Carbon and carbon nitride in-plane conjugated two-dimensional wave-absorbing material as well as preparation method and application thereof

    CN117143563A

  • Hollow foam material and preparation method and application thereof

    WO2018086522A1